The second part is right, but for e^x, the derivative is just e^x... d/dx (e^u) = e^u (du/dx) (don't forget, if the exponent is something besides just x, you need to use the chain rule)
The power reducing only works for a variable raised to a power. e, although it is a letter, is actually a number, or a constant, not a variable.
so, y' = e^x + e*x^(e-1)
2007-01-10 20:32:23
·
answer #1
·
answered by Jaqua 2
·
0⤊
0⤋
y' = e^x + e*x^(e-1)
2007-01-10 18:49:53
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
y= e^x + x^e
dy/dx = e^x + e.x^(e-1)
For the function e^x, the derivative is the same (i.e. e^x) by definition(try the MacLaurin expansion and differentiate term by term, or alternatively the fact that the function has a derivative the same as the function may be taken as a definition at elementary level.
Hope this helps!
2007-01-10 20:18:53
·
answer #3
·
answered by yasiru89 6
·
0⤊
0⤋
Given,
y = e^x + x^e
=> y' = e^x + ex^(e-1)
2007-01-10 19:36:00
·
answer #4
·
answered by rishi 2
·
0⤊
0⤋
That's right for the second half, not the first tho.
y' = e^x + ex^(e - 1)
The derivative of e^x is just e^x.
2007-01-10 18:47:08
·
answer #5
·
answered by Jim Burnell 6
·
0⤊
0⤋
e^x + ex^(e-1)
2007-01-10 19:01:53
·
answer #6
·
answered by gjmb1960 7
·
0⤊
0⤋
y = e^x + x^e
y' = e^x + ex^(e-1)
2007-01-10 20:06:46
·
answer #7
·
answered by Northstar 7
·
0⤊
0⤋
(e^x + x^e)' = e^x + e*x^(e-1)
you made it right
2007-01-10 20:01:07
·
answer #8
·
answered by James Chan 4
·
0⤊
0⤋